The Effect of the Hydroalcoholic Extract of Watercress on the Levels of Protein Carbonyl, Inflammatory Markers, and Vitamin E in Chronic Hemodialysis Patients - Moslem Sedaghattalab; Marzieh Razazan; Mohsen Shahpari; Nahid Azarmehr; Rozina Abbasi Larki; Hossein Sadeghi; Arash Asfaram; Tahere Taheri; Aminollah Pourshohod; Zahra Moslemi; Kazem Abbaszadeh-Goudarzi; Amir Hossein Doustimotlagh (Biochemistry Research International)
Introduction. Chronic kidney disorder is a main public health concern. Inflammatory processes and oxidative stress are common in end-stage renal disease patients. We aimed to evaluate the effect of the hydroalcoholic extract of watercress (WC) on the inflammatory cytokines and protein carbonyl (PCO) contents in chronic hemodialysis patients. Methods. This was a double-blind randomized clinical trial performed on 46 hemodialysis patients. The participants were randomly divided into two groups: intervention group (500 mg hydroalcoholic extract of WC every day for 4 weeks) and control group (500 mg of white flour every night for 4 weeks). The blood samples were taken to determine the levels of vitamin E, PCO, and inflammatory cytokines at baseline and the end of treatment. Results. Forty-five patients completed the study (22 patients in the intervention group and 23 patients in the control group). There was a significant reduction in the PCO level (20.33 ± 4.40 vs. 15.06 ± 6.41, P=0.001) in the intervention group; also, this change was statistically significant relative to the control group. Furthermore, there were significant reductions in hs-CRP (8953.30 ± 5588.06 vs. 7249.86 ± 5091.62, P=0.007) and IL-6 (60.10 (55.99, 73.10) vs. 55.21 (53.39, 60.48), P=0.050) in the intervention group, but these changes were not significant in comparison with the control group. Conclusion. We conclude that the hydroalcoholic extract of WC reduced the PCO content in hemodialysis patients via inhibition of protein oxidation. Although WC administration had caused a significant reduction in IL-6 and CRP levels, these differences were not statistically significant relative to the control group. Further research is needed to identify the antioxidant and anti-inflammatory effects of WC in hemodialysis patients.